Original paperPro-inflammatory activation of monocytes in patients with type 2 diabetes - Winiarska, Hanna; Bobkiewicz-Kozłowska, Teresa; Jagodziński, Paweł P.; Kempisty, Bartosz; Dworacka, Marzena (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2009)
Introduction: Monocytes isolated from type 2 diabetic subjects exhibit increased pro-inflammatory and pro-atherogenic activity. Tumor necrosis factor-a (TNF-α) secreted by monocytes seems to be a key cytokine inducing the progression of chronic inflammatory process and in consequence atherosclerosis. Aim: To evaluate whether TNF-α mRNA expression in monocytes is related to metabolic and anthropometric parameters which express therapeutic effects. Material and methods: Monocytes from 22 with type 2 diabetes and from 15 healthy subjects were isolated in order to assess the expression of TNF-α mRNA using real-time quantitative-PCR. All subjects were characterized with respect to metabolic (carbohydrate and lipid), anthropometric parameters (BMI, age) and TNF-α serum levels. Results: The monocyte TNF-α mRNA expression, as well as TNF-α plasma concentrations, were significantly higher in patients with type 2 diabetes comparing to healthy controls. In type 2 diabetic group the monocyte TNF-α mRNA expression was correlated with total cholesterol and LDL cholesterol serum levels. No correlation was found between other metabolic parameters, anthropometric markers, TNF-α serum level and TNF-α mRNA expression in monocytes. Conclusions: The results suggest that TNF-α mRNA expression in monocyte from type 2 diabetic patients is closely related to lipid profile deteriorations. Therefore prevention of chronic inflammation leading to atherosclerosis development could be provided by the intensive therapy of hyperlipidaemia.